Epidemiologi Penyakit Daun Disebabkan Jamur pada Tanaman Jagung di Kecamatan Indralaya Utara Kabupaten Ogan Ilir - Harman Hamidson; Suwandi Suwandi; Nurhayati Nurhayati (xxxx-xxxx, 2020)
Hamidson H, Suwandi S, Nurhayati N. 2020.  Epidemiology  of  leaves caused by fungi in corn plants in Indralaya Utara Ogan Ilir district. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang  20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aims to observe the development of disease in maize plants caused by fungi related to the epidemiology of leaves diseases caused by fungi in corn plants in Indralaya Utara District, Ogan Ilir Regency. The low production of maize is caused by the attack of plant-disturbing organisms from both pests and diseases. The survey results showed that two maize diseases were leaf blight and leaf rust. Leaf blight can reduce production by up to 50%. Leaf blight (Helminthosporium sp; Bipolaris sp; Exserohilum sp) and leaf rust disease (Puccinia sp). The highest incidence percentage was found in plants aged 60 DAS at 16.64%. The results of the seed health tests of the six types of corn seeds observed were Annom and Sukanegara seeds growing faster, Annom seeds growing faster on the surface of the seeds followed by Bisma, Lamuru, and Srikandi Kuning seeds. Annom seeds mostly carried seed fungi that grew on the seed surface followed by Bonanza seeds. Types of fungi carried by the seeds, namely Aspergillus sp; Penicellium sp; Trichoderma sp; Diplodia sp; and Bipolaris sp.